Spectroscopic Estimation of N Concentration in Wheat Organs for Assessing N Remobilization Under Different Irrigation Regimes - Li, Wei; Zhou, Xiaonan; Yu, Kang; Zhang, Zhen; Liu, Yang; Hu, Naiyue; Liu, Ying; Yao, Chunsheng; Yang, Xiaoguang; Wang, Zhimin; Zhang, Yinghua (Frontiers in Plant Science, 2021)
Nitrogen (N) remobilization is a critical process that provides substantial N to winter wheat grains for improving yield productivity. Here, the remobilization of N from anthesis to maturity in two wheat cultivars under three irrigation regimes was measured and its relationship to organ N concentration was examined. Based on spectral data of organ powder samples, partial least squares regression (PLSR) models were calibrated to estimate N concentration (Nmass) and validated against with laboratory-based measurements. Although spectral reflectance could accurately estimate Nmass, the PLSR-based Nmass-spectra predictive model was found to be organ-specific, organs at the top canopy (chaff and top three leaves) received the best predictions (R2 >0.88). In addition, N remobilization efficiency (NRE) in the top two leaves and top third internode was highly correlated with its corresponding N concentration change (ΔNmass) with a R2 of 0.90. ΔNmass of the top first internode (TIN1) explained 78% variation of the whole-plant NRE. This study provides a proof of concept for estimating N concentration and assessing N remobilization using hyperspectral data of individual organs, which offers a non-chemical and low-cost approach to screen germplasms for an optimal NRE in drought-resistance breeding.